1967
DOI: 10.1002/1097-0142(196711)20:11<1899::aid-cncr2820201116>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Morphogenesis of cervical cancer.Findings from San Diego County Cytology Registry

Abstract: The San Diego Cytology Registry collected results on cytology examinations on more than 180,000 women; more than 60,000 of these had multiple examinations. The age‐specific prevalence and incidence rates for suspicious and positive cytology and for dysplasia, carcinoma in situ and invasive cancer of the cervix are presented. These are analyzed in terms of the morphogenesis of cervical cancer. Carcinoma in situ reaches its maximum incidence rate among women aged 25 to 29. The rates then decrease and continue at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1
2

Year Published

1968
1968
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(16 citation statements)
references
References 3 publications
0
13
1
2
Order By: Relevance
“…However, these estimates vary between 5 and 16 years [13,[18][19][20][21][22][23][24][25]. Recent knowledge on the natural history of HPV infection, which is believed to be the initiating causal factor, indicates an even shorter duration of the pre-invasive phase [26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…However, these estimates vary between 5 and 16 years [13,[18][19][20][21][22][23][24][25]. Recent knowledge on the natural history of HPV infection, which is believed to be the initiating causal factor, indicates an even shorter duration of the pre-invasive phase [26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Estimates of the age-specific prevalence of dysplasia, carcinoma in situ (c.i.s.) and preclinical invasive disease in unscreened populations are available from several studies (Dunn & Martin, 1967;Bibbo et al, 1971;Fidler et al, 1968;Sweetnam et al, 1981;Parkin et al, 1982b). Prevalence of clinical cancer (women currently alive who have had a previous diagnosis of clinical cancer) must be estimated from incidence of clinical cancer prescreening, and survival rates for the same time period.…”
Section: Simulation Of Demographic Eventsmentioning
confidence: 99%
“…There has been a recent trend to the use of the terminology "cervical intra-epithelial neoplasia" (C.I.N.) for all pre-invasive abnormalities of the cervix (Richart & Barron, 1969;Koss, 1978 (Rotkin, 1973) or their partner (Skegg et al, 1982) The incidence of dysplasia (transfer 1 to 2) is derived from observed data (Dunn & Martin, 1967;Parkin et al, 1982b), and transition from clinical cancer to death (5 to 8) is derived from age/duration-specific survival rates for England and Wales (OPCS, 1980). Dysplasia is a relatively transient condition, and the high regression rates (2 to 1) used here (12.5-25% per year) are consistent with observed data (Stern & Neely, 1964;Fox, 1967;Nasiell et al, 1976).…”
Section: Simulation Of the Disease Processmentioning
confidence: 99%
“…The estimated average duration of dysplasia before it becomes carcinoma in situ is about 3.8 years, and the duration of carcinoma in situ before it develops into invasive carcinoma is estimated at 8.1 + years. 6 These are averages, and when dysplasia or carcinoma in situ is diagnosed it is often impossible for the clinician to ascertain how long the lesion has been present. Thus the need for examination of smears at close intervals in cases of dysplasia cannot be overemphasized.…”
Section: University Of Michigan Medical Centermentioning
confidence: 99%